PEMANFAATAN LIMBAH KULIT BUAH DURIAN DAN SERBUK GERGAJI MENJADI BRIKET SEBAGAI BAHAN BAKAR ALTERNATIF - Mohammad Mirwan; Rizal Adi Nugraha (EnviroUS, 2022)
Energy needs are currently increasing in the use of oil and gas fuels accompanied by increasing population growth, making people look for alternative fuel substitutes. Utilization of biomass waste can be used as raw material for alternative energy sources, namely briquettes. Briquettes with raw materials of durian peel waste and sawdust using molasses adhesive can be an alternative fuel. The purpose of this study is to reduce the environmental waste by reusing it and can be used as an alternative fuel as well as providing information about making briquettes and knowing the calorific value, compressive strength, moisture content, ash content, and flame test to produce the best briquettes. In this study, the comparison of durian peel waste with a mixture of sawdust 0:1, 1:0, 1:1, 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 with using 40% molasses adhesive. This research resulted in the highest calorific value with 5674.50 Cal/gr from a ratio of 1:0 on a 30 mesh with a flame duration of 55 minutes.